PACAP Neurons in the Ventromedial Hypothalamic Nucleus Are Glucose Inhibited and Their Selective Activation Induces Hyperglycaemia - Khodai, Tansi; Nunn, Nicolas; Worth, Amy A.; Feetham, Claire H.; Belle, Mino D. C.; Piggins, Hugh D.; Luckman, Simon M. (Frontiers in Endocrinology, 2018)
Abstract Background: Glucose-sensing neurons are located in several parts of the brain, but are concentrated in the ventromedial nucleus of the hypothalamus (VMH). The importance of these VMH neurons in glucose homeostasis is well established, however, little is known about their individual identity. In the present study, we identified a distinct glucose-sensing population in the VMH and explored its place in the glucose-regulatory network. Methods: Using patch-clamp electrophysiology on Pacap-cre::EYFP cells, we explored the glucose-sensing ability of the pituitary adenylate cyclase-activating peptide (PACAP) neurons both inside and outside the VMH. We also mapped the efferent projections of these neurons using anterograde and retrograde tracing techniques. Finally, to test the functionality of PACAPVMH in vivo, we used DREADD technology and measured systemic responses. Results: We demonstrate that PACAP neurons inside (PACAPVMH), but not outside the VMH are intrinsically glucose inhibited (GI). Anatomical tracing techniques show that PACAPVMH neurons project to several areas that can influence autonomic output. In vivo, chemogenetic stimulation of these neurons inhibits insulin secretion leading to reduced glucose tolerance, implicating their role in systemic glucose regulation. Conclusion: These findings are important as they identify, for the first time, a specific VMH neuronal population involved in glucose homeostasis. Identifying the different glucose-sensing populations in the VMH will help piece together the different arms of glucose regulation providing vital information regarding central responses to glucose metabolic disorders including hypoglycaemia.